(untitled) (Communications in Computational Physics, 2008)
To enhance the stability of traffic flow, a new car-following model is proposed by taking into account the support of intelligent transportation system (ITS) information, which includes both the headway and the velocity difference of multiple preceding cars. The new model is based on the Optimal Velocity (OV) model and its extended models. The stability condition of the model is obtained by using the linear stability theory. Through nonlinear analysis, the modified Korteweg-de Vries equation is constructed and solved, and the traffic flow is classified into three types, i.e. stable, metastable, and unstable. The jam phase can thus be described by the kink-antikink soliton solution for the mKdV equation. The numerical simulation results show that compared with previous models considering only one of the ITS information, the proposed model can suppress traffic jams more efficiently when both headway and velocity difference of arbitrary preceding cars are taken into account. The results of numerical simulation coincide with the theoretical ones.